Effect of salinity (NaCl) stress on physiological characteristics of rice (Oryza sativa L.) at early seedling stage - Shakeela, B. S.; Chachar, Q. I.; Chachar, S. D.; Solangi, A. B.; Solangi, J. A. (International Journal of Agricultural Technology, 2016)
Salinity is a common environmental stress seriously affecting crop growth, production and yield. This experiment was planned to study the effect of salinity stress on physiological characteristics of rice (Oryza sativa L.) at early seedling stage. The seeds four rice genotypes (IR88611-B-5, IR83142-B-61-B, IR -72 and FL-478) were grown on plastic boxes [nylon netted frame (5 x 7”) fitted in 2.5 L solution capacity] filled with culture solution. The pH of culture solution was maintained at 5.0. These boxes were placed separately in an incubator at 30oC up to ten days. Salinity cause decrease leaf area and potassium (K+) content of rice genotypes; although the genotypes behaved differently. However, membrane injury, chlorophyll content and total sugars of all rice genotypes increased under salinity stresses. A substantial increase in Na+ concentration was also observed in all genotypes due to increase in NaCl concentrations. Rice genotypes IR83142-B-61-B and IR -72 had maximum decrease in leaf area under salt stress, whereas, genotypes IR83142-B-61-B and IR -72 had higher proline accumulation. It was concluded that salinity decreased the growth of all tested rice genotypes; Furthermore, genotypes IR88611-B-5 and FL 478 were more tolerant to salt stress than genotypes IR83142-B-61-B and IR-72.